Molecular Identification, Chemical Composition, and In Vitro Anthelmintic Activity of Sargassum duplicatum Against Haemonchus contortus - Sakti, A. A.; Kustantinah,; Sofyan, A; Nurcahyo, R. W.; Fidriyanto, R.; Kusnadi, H.; Prasetyo, A.; Putnarubun, C.; Permadi, S.; Pramono,; Hartati, L.; Hudaifa, I.; et al. (Tropical Animal Science Journal, 2024)
The resistance of the Haemonchus contortus, a parasite causing severe anemia in ruminants, to commercial anthelmintics emphasizes the need for alternative bio-anthelmintics. This study aimed to identify the molecular, chemical composition, and in vitro anthelmintic activity of Sargassum duplicatum against H. contortus. Molecular identification employed the Chelex method, with DNA diversity and phylogeny assessed using maximum likelihood in IQ-tree. The analyzed chemical composition included proximate, total flavonoid, and total phenols. Adult worm motility test (AWMT) and egg hatch inhibiting test (EHIT) were conducted at concentrations of 2, 4, and 6 mg/mL of S. duplicatum ethanolic extract. AWMT followed a completely randomized factorial design (5 replications, each with 5 worms), while EHIT used a completely randomized one-way design (5 replications, each with H. contortus egg batches from 3 adult female worms). The cox1 gene sequence revealed the Sargassum sample as S. duplicatum (KP101270.1) with 99.83% similarity. The results indicated that the identified concentrations of S. duplicatum ethanolic extract, and the observation time significantly influenced motility and egg hatchability (p